Optimizing Inventory Management of MFD Studio To Reduce The High Lost Sales - Raka Aditya Prayoga; Nur Budi Mulyono (Integrasi Sains Media, 2024)
This research delves into optimizing inventory management at MFD Studio by implementing demand forecasting to mitigate lost sales. Notably, the company has encountered a significant loss of sales, approximately 31.26% of the revenue generated by their flagship product, Outer, which has consistently held the position of the best-seller from 2021 to 2023, contributing approximately 60% to MFD Studio's overall product line during this period. The research aims to enhance inventory management efficiency by employing demand forecasting techniques. The methodology includes a thorough literature review, analysis of root causes, and conceptual framework development. The findings underscore the substantial impact of demand forecasting on inventory management, leading to a noteworthy reduction in lost sales. The study advocates for adopting a quantitative approach to demand forecasting, explicitly endorsing the ARIMA, Holt, and Winter models. Notably, the ARIMA model stands out with the lowest error, boasting a 0.0059 RMSE value, 0.0025 MAE value, and 0.0363 MAPE value. The forecast generated by the ARIMA model is anticipated to diminish the likelihood of future lost sales to 5.5%, representing a substantial decrease from the initial 31.26%. In conclusion, this research underscores the pivotal role of demand forecasting as a crucial tool for businesses, particularly in similar industries, to enhance inventory management and curtail lost sales. The practical recommendations contribute significantly to inventory management, offering actionable insights for businesses seeking to optimize their inventory processes.